2016
DOI: 10.3390/s17010055
|View full text |Cite
|
Sign up to set email alerts
|

Honey Bee Colonies Remote Monitoring System

Abstract: Bees are very important for terrestrial ecosystems and, above all, for the subsistence of many crops, due to their ability to pollinate flowers. Currently, the honey bee populations are decreasing due to colony collapse disorder (CCD). The reasons for CCD are not fully known, and as a result, it is essential to obtain all possible information on the environmental conditions surrounding the beehives. On the other hand, it is important to carry out such information gathering as non-intrusively as possible to avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 28 publications
1
58
0
4
Order By: Relevance
“…The authors reported that the SVM approach provided a better generalization effect over the CNN. Zacepins et al [7], Gil-Lebrero et al [21] and Zacepins et al [22] proposed various acoustic monitoring systems for bees. The research area still has open questions [8], particularly if IoT architecture, accuracy and overall context questions are also considered.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that the SVM approach provided a better generalization effect over the CNN. Zacepins et al [7], Gil-Lebrero et al [21] and Zacepins et al [22] proposed various acoustic monitoring systems for bees. The research area still has open questions [8], particularly if IoT architecture, accuracy and overall context questions are also considered.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used systems for these types of threats are digital weight scales with GPRS or IEE802.15.4 transponders. These devices provide hive weight measurements and alarm systems if these measurement trends are out of scale [17][18][19][20]. If the beehive's weight fluctuates above thresholds, beekeepers are notified via SMS, or email or even 3G/4G HTTP push notifications.…”
Section: Iot Beehive Security Systemsmentioning
confidence: 99%
“…(Fitzgerald et al;2015;Ruan et al;. De forma mais abrangente, temperatura, umidade relativa e massa podem ser combinados para checagem da termorregulação e evolução da colônia na época de oração (Gil-Lebrero et al; As técnicas de análise de componentes principais (PCA -Principal Component Analysis) e de análise de função discriminante (DFA -Discriminant Function Analysis) tem sido aplicadas em dados de vibração das colm4ias para identi cação de abandono iminente (Bencsik et al; 2011) e ciclo de produção das crias 2015).…”
Section: Trabalhos Correlatosunclassified
“…Trabalhos recentes têm registrado reduções no número de espécies polinizadoras silvestres e domesticadas e nos serviços de polinização em todo o mundo . Nos últimos anos, populações de abelhas da espécie Apis mellifera têm sofrido mortes em massa em regiões da Europa e da Améria do Norte devido ao fenômeno da desordem do colapso da colônia (colony collapse disorder -CCD) (Barron;2015;Chauzat et al;Gil-Lebrero et al;. Esse fenômeno se caracteriza pela rápida perda de abelhas operárias, evidenciada pelo enfraquecimento ou morte da colônia com excesso de crias, em comparação ao número de abelhas adultas; ausência de crias e abelhas adultas mortas dentro ou fora da colmeia; e invasão da colmeia por pragas (Pires et al;.…”
Section: Introductionunclassified